Parenting Schools Contribution to Student Learning Outcomes in Elementary School Civic Education Subjects - Kartini Kartini (Council: Education Journal of Social Studies, 2023)
This research aims to determine the contribution of parenting school to students' learning outcomes in the Civic Education subject at SDN No. 25 Panaikang, Bissappu Sub-District, Bantaeng Regency. This study is of quantitative nature, utilizing a survey method with correlational techniques. Data collection was carried out through observation, documentation, and questionnaires. The results of this study indicate: (1) The applied Parenting School to students at SDN No. 25 Panaikang, Bissappu Sub-District, Bantaeng Regency, based on student data, categorized 62 students (95.4%); (2) The learning outcomes of students at SDN No. 25 Panaikang, Bissappu Sub-District, Bantaeng Regency, are categorized as high for 13 students (20%), medium for 41 students (63.1%), and low for 11 students (16.9%), resulting in an overall medium learning outcome; (3) There is a contribution of parenting school to students' learning outcomes at SDN No. 25 Panaikang, Bissappu Sub-District, Bantaeng Regency. This can be observed from the research results regarding parenting school's influence on learning outcomes, where the calculated r value is greater than the tabled r value (0.375 > 0.244) and the coefficient of determination is 0.141, indicating a positive and significant contribution of 51.1%.